Pressure in underwater spark discharge initiated with the help of bubble injection and its evaluation based on H-alpha line broadening. (13th July 2023) - Frolov, Alexandr; Stelmashuk, Vitaliy; Kolacek, Karel; Prukner, Vaclav; Tuholukov, Andrii; Hoffer, Petr; Straus, Jaroslav; Schmidt, Jiri; Jirasek, Vit; Oliva, Eduardo
Abstract: The pressure in an underwater discharge channel is the main parameter that influences all its applications. In this study, we investigate a relatively large gap with a plane-to-plane electrode geometry that uses the assistance of an injected gas bubble for breakdown. The delay in the application of high voltage following the injection of a gas bubble from a grounded electrode determines the initial dimensions of the bubble. We examined three types of discharge: (a) a large bubble with easy triggering, (b) a medium bubble, and (c) a small bubble with difficult triggering. The main diagnostic tool is H α line broadening. It is shown that (i) Doppler broadening plays no role; (ii) at pressure broadening, the resonance and van der Waals broadenings must be considered; (iii) the impact approximation is not applicable, and hence the quasi-static high-pressure (namely 'nearest neighbour') approximation must be used; and (iv) the Stark broadening plays the dominant role. Because a mixture of two gases (evaporated water vapour and nitrogen from bubble injection) is present in the discharge channel, simple thermodynamic considerations were applied to estimate the ratio of the contributions of resonance and van der Waals broadening. The larger the bubble, the smaller the pressure detected in the discharge channel. This is in agreement with the measurements of the pressure wave amplitude at a certain distance from the discharge channel using a piezoelectric pressure probe.